تحليل أبعاد سلوكيات المواطنة التنظيمية لعينة من تدريسي جامعة بغداد - حسون شفاء محمد علي (Journal of Economics and Administrative Sciences, 2009)
The research considers The Analysis Dimensions of The organizational citizen ship Behavior for a sample of the Faculty of the university of Baghdad through the five Dimensions of citizenship ((Altruism– couscientiosness– sportsmanship courtesy– civic virtue)) The sample contains (120) professor from four colleges of the Baghdad university. The most Important conelusion is the rise of citizenship behavior level for the Iraqi professor through his generaliaed compliance for most dimensions of the citizenship behavior the most important recommanelations presenteel in research is the encouragement and development for this behavior because of its oby viosis impact on the performance of all the organizations espically the universities .